Effects of Pharmacological Inhibitors of NADPH Oxidase on Myogenic Contractility and Evoked Vasoactive Responses in Rat Resistance Arteries - Kendrick, Dylan J.; Mishra, Ramesh C.; John, Cini Mathew; Zhu, Hai-Lei; Braun, Andrew P. (Frontiers in Physiology, 2022)
Reactive oxygen species (ROS), such as superoxide anions and hydrogen peroxide, are reported to contribute to the dynamic regulation of contractility in various arterial preparations, however, the situation in pressurized, myogenically active resistance arteries is much less clear. In the present study, we have utilized established pharmacological inhibitors of NADPH oxidase activity to examine the potential contribution of ROS to intrinsic myogenic contractility in adult Sprague Dawley rat resistance arteries and responses to vasoactive agents acting via the endothelium (i.e. acetylcholine, SKA-31) or smooth muscle (i.e. sodium nitroprusside, phenylephrine). In cannulated and pressurized cremaster skeletal muscle and middle cerebral arteries, the NOX inhibitors 2-acetylphenothiazine (2-APT) and VAS2870, selective for NOX1 and NOX2, respectively, evoked concentration-dependent inhibition of basal myogenic tone in a reversible and irreversible manner, respectively, whereas the non-selective inhibitor apocynin augmented myogenic contractility. The vasodilatory actions of 2-APT and VAS2870 occurred primarily via the vascular endothelium and smooth muscle, respectively. Functional responses to established endothelium-dependent and –independent vasoactive agents were largely unaltered in the presence of these NOX inhibitors. In cremaster arteries from Type 2 Diabetic (T2D) Goto-Kakizaki rats with endothelial dysfunction, treatment with either 2-APT or apocynin did not modify stimulus-evoked vasoactive responses, but did affect basal myogenic tone. These same NOX inhibitors produced robust inhibition of total NADPH oxidase activity in aortic tissue homogenates from control and T2D rats, and NOX isozymes 1, 2 and 4, along with superoxide dismutase 1, were detected by qPCR in cremaster arteries and aorta from both species. Based on the diverse effects that we observed for established, chemically distinct NOX inhibitors, the functional contribution of vascular NADPH oxidase activity to stimulus-evoked vasoactive signaling in myogenically active, small resistance arteries remains unclear.